2020
DOI: 10.1038/s41467-020-19453-x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct oligodendrocyte populations have spatial preference and different responses to spinal cord injury

Abstract: Mature oligodendrocytes (MOLs) show transcriptional heterogeneity, the functional consequences of which are unclear. MOL heterogeneity might correlate with the local environment or their interactions with different neuron types. Here, we show that distinct MOL populations have spatial preference in the mammalian central nervous system (CNS). We found that MOL type 2 (MOL2) is enriched in the spinal cord when compared to the brain, while MOL types 5 and 6 (MOL5/6) increase their contribution to the OL lineage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
149
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(164 citation statements)
references
References 70 publications
(146 reference statements)
15
149
0
Order By: Relevance
“…According to their region of origin and their expression profile, OPCs can respond to various insults [ 42 , 43 ]. In agreement with the diversity of oligodendrocytes, transcriptomic profiles using high-throughput methods and single-cell RNA sequencing revealed different subpopulations of oligodendrocytes from several brain regions of juvenile and adult mouse brain [ 44 ] and in response to spinal cord injury [ 45 ]. Gene expression studies have also identified subpopulations of oligodendroglial cells in human adult white matter and fetal brain [ 35 , 36 , 46 ].…”
Section: The Oligodendroglial Cells and Myelination Processmentioning
confidence: 89%
“…According to their region of origin and their expression profile, OPCs can respond to various insults [ 42 , 43 ]. In agreement with the diversity of oligodendrocytes, transcriptomic profiles using high-throughput methods and single-cell RNA sequencing revealed different subpopulations of oligodendrocytes from several brain regions of juvenile and adult mouse brain [ 44 ] and in response to spinal cord injury [ 45 ]. Gene expression studies have also identified subpopulations of oligodendroglial cells in human adult white matter and fetal brain [ 35 , 36 , 46 ].…”
Section: The Oligodendroglial Cells and Myelination Processmentioning
confidence: 89%
“…First described in neurons, it is now widely accepted that also glial cells are characterized by a great diversity. In particular, in vivo clonal analysis and single-cell RNAseq have revealed both molecular and behavioral heterogeneity among OL lineage [ 8 , 46 , 47 , 48 ].…”
Section: Oligodendrocyte Functions In Adult Cnsmentioning
confidence: 99%
“…A clear segregation of cells between control and Experimental Autoimmune Encephalomyelitis (EAE) mice, the most commonly used model of multiple sclerosis (MS), has been demonstrated, with specific EAE-enriched OPCs and mature OLs populations that expressed unique genes which were completely absent or present at a very low level in healthy controls [ 8 ]. Interestingly, a very recent paper published by the same group demonstrated that, in a mild model of traumatic spinal cord injury (SCI), two transcriptionally diverse populations of mature OLs respond differently to injury [ 48 ]. Indeed, one population increased in corticospinal tract from juvenile to adulthood and pronominally contributed to the OL lineage at the injury site after SCI, whereas the other one was preferentially identified in sensory tracts of the spinal cord and participated in the OL lineage in regions of Wallerian degeneration specifically during the chronic phase [ 48 ].…”
Section: Oligodendrocyte Functions In Adult Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…These powerful methods provide unique insights into health and disease in contrast to bulk transcriptomic and classical histological analyses. Single-cell RNA-sequencing and spatial transcriptomic approaches have shown that glia isolated from healthy and disease-associated brain regions respond across broad cellular states for microglia (Tay et al, 2018;Hammond et al, 2019;Jordão et al, 2019;Li et al, 2019;Masuda et al, 2019), astrocytes (Cahoy et al, 2008;Zamanian et al, 2012;Boisvert et al, 2018;Bradley et al, 2019;Batiuk et al, 2020;Bayraktar et al, 2020;Das et al, 2020), and oligodendrocytes (Jäkel et al, 2019;Spitzer et al, 2019;Floriddia et al, 2020). Advances in single-cell proteomics have also enabled the highthroughput investigation of key biological questions involving protein binding, modifications, and degradation, that cannot be assessed at the transcriptomic level (Slavov, 2020).…”
Section: Current Approaches To Study Glial Heterogeneitymentioning
confidence: 99%